การพัฒนาระบบการวัดผลการปฏิบัติงานแบบดุลยภาพ : กรณีศึกษาบริษัทนายหน้าประกันภัย - เยาวภา เทียมถม (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
To develop the performance measurement system of the insurance broker by Balanced Scorecard. This is the result of huge competition amongst the non-life insurance market nowadays. Increased number of new insurance brokers is also another factor that leads to the need of developing the potential of competition so that the organization will have the clear direction to develop this ability for the competition The procedures of this development started from study insurance business’s environment and analysis of strengths, weaknesses, opportunities and treats of the organization. After that, vision, mission, critical success factors and strategic objectives were set to create strategic map, Key Performance Indicators (KPIs), targets and strategic initiatives. Then, strategies were deployed to the operation level. After developing the performance measurement system, we have implemented this system in reinsurance and financial and accounting department. There were 50% of KPIs of department level that achieve targets.